Preparation and Taste Profiling of the Enzymatic Protein Hydrolysate from a by-Product of Red Snow Crab Processing as a Natural Seasoning Compound - Ga-Yang Lee; Min-Jeong Jung; Jong-Woong Nam; Ah-Ram Han; Byoung-Mok Kim; Joon-Young Jun (Foods, 2022)
The red snow crab (Chionoecetes japonicus) is the most industrially processed in the Republic of Korea, and the meat is very popular, owing to its savory taste and flavor. Its body meat production comprises a two-step separation to increase meat yield. However, during the secondary separation, broken shell debris is occasionally entrained in the meat products, which is a concern for manufacturers. As the residues from first separation contain 39.9% protein, it can be utilized as an enzymatic protein hydrolysate (FPH) rich in free amino acids (FAAs). A combination of flavourzyme and alcalase (1:1) superiorly hydrolyzed the protein of the residues, and the best hydrolysis condition was suggested at 60 °C for 15 h with fourfold water and 2% enzyme addition, achieving a 57.4% degree of hydrolysis. The EPH was mostly composed of FAAs containing most essential amino acids; however, bitter-tasting amino acids accounted for 46.4% of the FAAs. To reduce the bitter taste, different nonvolatile organic acids were considered as masking agents, and citric and malic acids were effective, though the umami taste is slightly decreased. In conclusion, the crab processing residues can be utilized as an FAA-based natural seasoning compound through enzymatic hydrolysis and organic acid treatment.